Efficiency in urban governance to enhances competitiveness of city region - Jusoh, Hamzah; Abdul Rashid, Azmizam (2008)

(untitled)
This paper discusses on the preliminary study on efficiency in urban governance towards enhancing competitiveness of the city. The focus of this paper is to analyse the literature review on the concept of efficiency in urban governance. Preliminary discuss with selected local authorities in Klang Valley has been carried out to gain their understanding on the efficient urban governance. Malaysia has successfully applied economic planning to guide the development of the country from an economy of agriculture and mining to a largely industrialised one. Now, with its sights set on attaining the economic level of a fully developed nation by 2020, the planning system must be made even more efficient and focused. The country must focus on securing a credible share of the lead sectors of the globalised economy. The country must also be fully aware of the enormous competition it faces in a region with rapidly expanding and modernising economies, all contending for the same pool of potential international investments. The urban sector is an important catalyst towards national economic growth and a vital investment centre for the nation. Efficient urban governance is characterized by sustainability, subsidiarity, equity, efficiency, transparency and accountability, civic engagement and citizenship, and security. In line with this, the importance of efficient urban governance is eminent in administration of developing city like Kuala Lumpur City Region. Efficient urban governance is also fundamental issue in development.